Wage formation and gender wage gaps: The changing role of human capital in the Finnish technology industry - Rita Asplund; Reija Lilja (The Research Institute of the Finnish Economy (ETLA), 2010)
Both academia and policymakers express a strong belief in higher average education levels exerting a narrowing impact on wage inequality in general and gender wage gaps in particular. The present paper scrutinizes whether or not this effect extends to R&D- and export-intensive branches such as the technology industry. The answer seems to be a cautious 'no'. Indeed, while changes in standard human capital endowments can explain little, if anything, of the growth in real wages or the widening of wage dispersion among the Finnish technology industry's white-collar workers, a new job task evaluation scheme introduced in 2002 seems to have succeeded, at least in part, to make the wage-setting process more transparent by re-allocating especially the industry's female white-collar workers in a way that better reflects their skills, efforts and responsibilities. One crucial implication of this finding is that improving the standard human capital of women closer to that of men will not suffice to narrow the gender wage gap in the advanced parts of the economy and, hence, not also the overall gender wage gap. The reason is obvious: concomitant with rising average education levels, other skill aspects have received increasing attention in working life. Consequently, a conscious combination of formal and informal competencies as laid down in well-designed job task evaluation schemes may, in many instances, offer a more powerful path to tackling the gender wage gap.
Keywords: J16; J31; 330; decomposition; gender wage gap; human capital; job task evaluation; technology industry; wage formation